Narrativas sobre comunicación, límites y normas familiares desde la perspectiva de progenitoras de adultos sindicados por el delito de hurto calificado (2019)
This research aims to describe the narratives about communication, limits and family norms from the perspective of parents of syndicated adults for the crime of qualified theft. For the above, a qualitative methodology with epistemic references of social constructionism was designed, for the collection of information the open interview with guiding questions was used, six parents were involved, the research had a descriptive scope aimed at describing in detail narrative design, these stories are told with the same words, arguments and styles that the actors of those experiences use to order them, grant them meaning and value.